A FORMAÇÃO CONTINUADA DO DOCENTE NO ENSINO FUNDAMENTAL - Hellen Thaís dos Santos; Marcelo Vinícius Creres Rosa; Fátima Regina Preti; Tereza de Jesus Ferreira Scheide; Everton Tomiazzi; Maria Cristina Ponçano Brito; Sandra Regina Caseiro (Universidade do Oeste Paulista, 2011)
This article presents the results of the survey conducted among elementary school teachers belonging to Pirapozinho Division Municipal, State of Sao Paulo. The study aimed to identify the understanding of aspects of continuing education in the face of initial training from the perspective of teachers. As a result, was considered the need for continued education and has been proposed as the discussion of in-service.